2005
DOI: 10.1073/pnas.0500803102
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of herpesvirus capsid transport in axons is coupled to association with specific sets of tegument proteins

Abstract: The capsids of neurotropic herpesviruses have the remarkable ability to move in specific directions within axons. By modulating bidirectional capsid transport to favor either retrograde (minusend) or anterograde (plus-end) motion, these viruses travel to sensory ganglia or peripheral tissue at specific stages of infection. By using correlative motion analysis to simultaneously monitor the trafficking of distinct viral proteins in living neurons, we demonstrate that viral ''tegument'' proteins are complexed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
281
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(305 citation statements)
references
References 39 publications
24
281
0
Order By: Relevance
“…Although previous studies have demonstrated the role of other proteins in the egress of capsids from the nucleus and transport from nuclear envelope to vesicles in the cytoplasm of cultured cells (Luxton et al, 2005), we have identified a specific protein, Us9, which is necessary for the efficient polarized, anterograde transport of viral capsid and DNA in vivo. As found by others, Us9 is not necessary for the polarized retrograde transport of virus (Polcicova et al, 2005;Brideau et al, 2000).…”
Section: Polarized Anterograde Axonal Transportmentioning
confidence: 71%
“…Although previous studies have demonstrated the role of other proteins in the egress of capsids from the nucleus and transport from nuclear envelope to vesicles in the cytoplasm of cultured cells (Luxton et al, 2005), we have identified a specific protein, Us9, which is necessary for the efficient polarized, anterograde transport of viral capsid and DNA in vivo. As found by others, Us9 is not necessary for the polarized retrograde transport of virus (Polcicova et al, 2005;Brideau et al, 2000).…”
Section: Polarized Anterograde Axonal Transportmentioning
confidence: 71%
“…The viral envelope is removed from the capsid when it fuses with the cell membrane during entry. Much of the tegument also dissociates from the capsid upon entry and during transit to the nucleus (18,19,32,33,43). We have described tegument that is released from the capsid as loosely associated tegument and tegument that remains capsid bound (VP1/2 and UL37) as tightly associated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the axons of sensory neurons, incoming HSV capsids are moved by retrograde transport, whereas newly assembled capsids undergo bidirectional and salutatory motions, indicating a modulation of the plus-end directed motility 46 . This modulation involves HSV tegument proteins [47][48][49][50][51] , the removal of which precedes the retrograde transport of the incoming capsids to the cell body, whereas the addition is coupled to anterograde transport of progeny capsids to the distal axon 52,53 . Important signalling events might occur during viral transport.…”
Section: Viral Transportmentioning
confidence: 99%